A kinetic approach to predict soil trace metal bioavailability: preliminary results - Bermond, A.; Varrault, G.; Sappin-Didier, V.; Mench, M. (Plant and Soil, 2005)
The presence of large amounts of trace metals creates a hazard in some soils that is strongly related to the speciation of these metals. The aim of this work was to apply an operationally defined fractionation based on kinetics, which could distinguish ‘‘labile’’ (quickly extracted) and ‘‘non-labile’’ (or slowly labile i.e. slowly extracted) cations by using the extraction kinetics of trace metals by EDTA. This kinetic fractionation was applied to 10 unpolluted soil samples from Burgundy (France) in order to determine their labile concentrations of lead and cadmium. According to this method, cadmium was found to be more mobile than lead, with respect to both labile concentration and the kinetic constants. Moreover, it was also found that the labile concentration of cadmium was related (R-2 = 0.6) to its concentration in wheat shoots; however, no such correlation was found for lead.